Hong Kong Drug Allergy Delabelling Initiative (HK-DADI) consensus statements for penicillin allergy testing by nonallergists - Li, Philip H.; Wong, Jane C. Y.; Chan, Jacky M. C.; Chik, Thomas S. H.; Chu, M. Y.; Ho, Grace C. H.; Leung, W. S.; Li, Timothy C. M.; Ng, Y. Y.; Shum, Rocky; Sin, Winnie W. Y.; Tso, Eugene Y. K.; et al. (Frontiers in Allergy, 2022)
Introduction Penicillin allergy testing has been traditionally performed by allergists, but there remains a huge deficit of specialists. A multidisciplinary effort with nonallergists would be invaluable to overcome the magnitude of penicillin allergy labels via the Hong Kong Drug Allergy Delabelling Initiative (HK-DADI). These consensus statements (CSs) offer recommendations and guidance to enable nonallergists to screen for low-risk (LR) patients and perform penicillin allergy testing. Methods CSs were formulated by the HK-DADI Group using the Delphi method. An agreement was defined as greater than or equal to 80% consensus. Results A total of 26 CSs reached consensus after multiple rounds of Delphi. CSs were categorized into risk assessment, skin testing, drug provocation testing (DPT), and post-testing management. For risk assessment, the essentials of allergy history and exclusion criteria were detailed. Patients with only LR features can proceed with testing by nonallergists. Skin tests should be performed prior to DPT. Details regarding the timing, preparation, and interpretation of skin tests were elaborated. DPT remains the gold standard to diagnose genuine allergy or tolerance and should be performed when there is a low pretest probability following negative skin testing. Details of DPT preparations, dosing protocols, and interpretation were elaborated. For post-testing management, inaccurate allergy labels should be delabeled following negative DPT with proper patient counseling. Conclusion CSs support penicillin allergy testing by nonallergists in Hong Kong. LR cases can be managed by nonallergists at Spoke Clinics, with training and support of an allergist-led Hub.